Chronic restraint stress impairs sociability but not social recognition and spatial memoryin C57BL/6J mice - Zain, Mohd Aizat Mohd; Pandy, Vijayapandi; Majeed, Abu Bakar Abdul; Wong, Won Fen; Mohamed, Zahurin (Japanese Association for Laboratory Animal Science, 2019)
Chronic stress has been associated with impairment of memory, learning, and social cognition. In animal studies, chronic stress has been shown to impair rodent sociability behaviour which mimics social withdrawal as observed in depression patients. The effect of chronic stress on social recognition, however, is uncertain. Moreover, with reference to spatial learning and memory, the effect of chronic stress is dependent on the type of behavioural task: an appetitively or aversively motivated tasks. The effect of chronic stress was consistent in impairing spatial learning and memory in the appetitive task; however, the effect was inconsistent in an aversive task like the Morris water maze. Thus, we aimed to investigate the effect of chronic restraint stress on sociability and social recognition by using a modified protocol of the three-chamber paradigm and the effect of chronic restraint stress on spatial learning and memory by using the Morris water maze test in young adult C57BL/6J male mice. The present report also describes a modified protocol of the three-chamber paradigm. Our modification is based on measurement of sniffing behaviour, which is a direct social interaction that represents sociability. We used the chronic restraint stress paradigm for 6 h/day for 21 days to induce depression-like symptoms in male C57BL/6J mice which were validated by forced-swim test. We observed that the stressed group had impairments in their sociability behaviour but that social recognition was not affected. Furthermore, we confirmed that chronic stress produced no significant impairment in spatial learning and memory of the mice in the water maze.